KONTRIBUSI SISTEM DUKUH TERHADAP ASPEK SOSIAL EKONOMI, SOSIAL BUDAYA DAN LINGKUNGAN DI DESA KIRAM KABUPATEN BANJAR - Krisna Irawan; Mahrus Aryadi; Setia Budi Peran; Yudi Ahmad Nazari (EnviroScienteae, 2015)
This study aimed to explore the contribution of social economy value, the level of involvement of community members from a gender perspective, and to explore the amount of carbon that sequestrated from the dukuh management. Direct observation and open interviews were the methods that were carried out to collect information from the owners of dukuh and key informants. The results showed that dukuh contributed 54,84% of the total annual income. Dukuh management was mostly conducted by men and women of 46,67% and 37,18%, respectively. All family members of both men and women had the equal rights and responsibility in sustaining the dukuh management. The total number of carbon stocks in the dukuh management was 213,20 tons/ha. The number of above ground carbon stocks was bigger than below ground carbon stocks of 65,25% and 34,74%, respectively.